Conservative Politics in National and Imperial Crisis : Letters from Britain to the Viceroy of India 1926-31. - Ball, Stuart (Ashgate Publishing Ltd, 2014)
Whilst serving in the prestigious post of Viceroy of India (1926-1931), Lord Irwin (later the Earl of Halifax) was kept informed about political events in Britain by frequent letters from shrewd political insiders. These private and previously unpublished letters offer a frank account from within the highest political circles of the Baldwin government (1924-29) and the serious crisis in the Conservative Party which followed (1929-31). Of great depth and richness, this collection is an essential historical source for British history between the two World Wars.